Webinar satisfaction factors in the stories of participants - Radoslaw, Czahajda (International journal of training and development, 2022)
The purpose of this study was to explore the factors that affect participants' webinar satisfaction, with special emphasis on the dissatisfaction factors. The method of empathy‐based stories was chosen for the research due to its potential to eliminate bias from other qualitative methods. The research collected 280 different factors potentially impacting training satisfaction. Some of them had not been raised in subject literature before. In contrast to previous studies, this research concluded that the length of the webinar and finding it interesting might not be critical from the participants' point of view. Moreover, participants of the study valued the depth of content more than breadth. The research also discovered a potentially disregarded important satisfaction factor of webinar description, shaping participants' expectations.